2013
DOI: 10.1371/journal.pone.0070282
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Electrical Pain Threshold by Voluntary Breathing-Controlled Electrical Stimulation (BreEStim) in Healthy Subjects

Abstract: BackgroundPain has a distinct sensory and affective (i.e., unpleasantness) component. BreEStim, during which electrical stimulation is delivered during voluntary breathing, has been shown to selectively reduce the affective component of post-amputation phantom pain. The objective was to examine whether BreEStim increases pain threshold such that subjects could have improved tolerance of sensation of painful stimuli.MethodsEleven pain-free healthy subjects (7 males, 4 females) participated in the study. All sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 33 publications
11
26
2
Order By: Relevance
“…We further systematically compared the analgesic effects between BreEStim and conventional EStim to a peripheral nerve, or voluntary breathing only on experimentally induced pain in healthy subjects. We observed that BreEStim resulted in a general desensitization effect (measured by elevated electrical pain thresholds in both treated and nontreated hands), while there was no such effect, or even a general sensitization effect after EStim or voluntary breathing only 1719. The findings support preliminary clinical observations15,16 that BreEStim-induced analgesia is likely related to modification of the affective component, ie, central effect.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…We further systematically compared the analgesic effects between BreEStim and conventional EStim to a peripheral nerve, or voluntary breathing only on experimentally induced pain in healthy subjects. We observed that BreEStim resulted in a general desensitization effect (measured by elevated electrical pain thresholds in both treated and nontreated hands), while there was no such effect, or even a general sensitization effect after EStim or voluntary breathing only 1719. The findings support preliminary clinical observations15,16 that BreEStim-induced analgesia is likely related to modification of the affective component, ie, central effect.…”
Section: Introductionsupporting
confidence: 85%
“…These settings and protocols were similar to our recent series of BreEStim experiments 1719. Technical details of BreEStim are available online in a methodology video article: http://www.jove.com/video/50077/ 15…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…There was no difference in the intensity of electrical stimulation between EStim and BreEStim in the present and previous [21] studies. Therefore, the habituation effect of BreEStim is likely attributable to the effect associated with voluntary breathing.…”
Section: Discussioncontrasting
confidence: 51%
“…Following unilateral electrical median nerve stimulation, there was bilateral activation of primary somatosensory cortex [22] and increased pain threshold of the contralateral index finger [23]. In contrast, the sensitization effect was seen in both stimulated and contralateral symmetrical area after EStim in the previous study [21]. In the present study, we aimed to compare BreEStim and EStim by examining these factors (nerve stimulation vs. acupuncture, unilateral vs. contralateral or systemic effects).…”
Section: Introductionmentioning
confidence: 79%